Identifying Students’ Conceptions on Sound Wave via the Sound Wave Four Tier (SOFT) Diagnostic Test - Amalia Weka Gani; Achmad Samsudin; Lina Aviyanti; Adam Hadiana Aminudin; Fatah Kurniawan; Muhammad Zahran; Jajang Kunaedi; Hasan Ozgur Kapici (Universitas Lambung Mangkurat, 2023)
This paper aimed to assess the validity of the Sound Wave Four Tier (SOFT) Diagnostic Test that can be used to identify students' conception profiles. Using the Four Design (The participants were 42 students aged 15-17 years old in one of the public high schools in Bandung City. The participants were 42 students aged 15-17 in one of the public high schools in Bandung City. The data's validity, the instrument's reliability, and the distribution of students' conceptions were analyzed using the Rasch model with the MINISTEP 4.5.3.0 program. The dimensional-based validity of the items used was valid. Accuracy based on Cronbach Alpha (α) was in the high category, the item reliability score was in the good category, and the reliability of personnel was in the low category. The conception profile of the students categorized as. Sound Understanding (SU), Partial Positive (PP), Partial Neutral (PNt), Partial Negative (PNg), Misconception (MC), No Understanding (NU), and No Coding (NC). The highest category of conception found was MC. There were a lot of misconceptions found in the sound wave material. Students' Misconceptions are still commonly found in sound waves. A 4D model can be developed using Rasch modeling analysis to identify students' profiles. Utilizing the SOFT instrument enables students to gain a broader understanding of the concept, including verbal statements and various representations of images and mathematical symbols.